TÜRKMEN YAZAR ÖVEZDURDU NEPESOV'UN "UZAK UZAK YILLAR" ROMANININ YAPI VE TEMA BAKIMINDAN İNCELENMESİ - ÇAĞLAR, YASİN (Fırat Üniveristesi, 2021)
Çağdaş Türkmen Edebiyatı'nın en önemli şair ve yazarlarından biri olan Övezdurdu Nepesov, birçok şiir, roman, hikâye ve tiyatro gibi eserler vermiştir. Çağdaş Türkmen Edebiyatı'nın gelişmesinde önemli rol üstlenmiştir. Bu çalışmada Övezdurdu Nepesov'un "Uzak Uzak Yıllar" adlı romanının yapı ve tema bakımından incelemesi yapılmıştır. Övezdurdu Nepesov bu romanla Türkmen sosyo-kültürel hayatına, tarihine ışık tutmuş ve modernist bir anlayışla Türkmen romanının gelişmesine katkıda bulunmuştur. Romanın başkarakteri olan İlaman'ın başından geçen olaylar kronojik zaman dilimi içinde ele alınmıştır.

Övezdurdu Nepesov, one of the most important poets and writers of Contemporary Turkmen Literature, has produced many works such as poems, novels, stories and plays. He has played an important role in the development of Contemporary Turkmen Literature. In this study, Övezdurdu Nepesov's novel named "Far Far Years" was examined in terms of structure and theme. Övezdurdu Nepesov shed light on Turkmen socio-cultural life and history with this novel and contributed to the development of the Turkmen novel with a modernist understanding. The events of Ilamen, the protagonist of the novel, are discussed in chronological time frame.
Examination of Turkmen author Övezdurdu Nepesov's novel named as "Uzak Uzak Yıllar" in the terms of structure and theme
Keywords: Türk Dili ve Edebiyatı